Stability of thin quasi-crystalline Ti-Zr-Ni films and related crystalline phases under low-energy transient plasma irradiation - Malykhin, S.V.; Kondratenko, V.V.; Makhlai, V.A.; Garkusha, I.E.; Kopylets, I.A.; Borisov, Yu.S.; Herashchenko, S.S.; Surovitskiy, S.V.; Borisova, S.S. (Problems of Atomic Science and Technology, 2022)
The properties of Ti41Zr38.3Ni20.7 thin films under radiation-thermal action of hydrogen plasma with a surface heat load of 0.2 MJ/m² was studied at the QSPA Kh-50 quasi-stationary plasma accelerator (NSC KIPT). The phase composition, structural state, and surface morphology were studied using X-ray diffraction and scanning electron microscopy. It was found that the quasicrystalline phase and related crystalline phases, the Laves phase, the α-solid solution, and the 2/1 phase of the Ti-Zr-Ni approximant crystal were stable under irradiation with up to 20 hydrogen plasma pulses. The phase composition did not change. It is shown that the changes in the coatings mainly manifest themselves as changes in the substructure of the observed phases. With an increase in the plasma exposure dose, the structure of the quasicrystalline icosahedral phase improves, and the size of the coherence regions increases. In the films consisting of crystalline phases, a partial phase transformation is observed with a redistribution of components between the 2/1 phase of the approximant crystal and the α-solid solution phase. It was found that thin films of the Ti-Zr-Ni system containing a quasicrystalline icosahedral phase, irradiated with radiation-thermal plasma pulses, are less prone to cracking than coatings with crystalline phases of the same system. На квазістаціонарному плазмовому прискорювачі КСПП Х-50 (ННЦ ХФТІ) досліджено характеристики тонких плівок Ti41Zr38.3Ni20.7 при радіаційно-термічному впливі водневої плазми з тепловим навантаженням на поверхню 0,2 МДж/м². Фазовий склад, структурний стан та морфологія поверхні були досліджені методами рентгенівської дифракції та скануючої електронної мікроскопії. Встановлено, що квазікрісталічна фаза, а також споріднені з нею кристалічні фази: фаза Лавеса, α-твердий розчин і фаза 2/1 кристала-апроксиманта Ti-Zr-Ni-системи виявилися стійкими при опроміненні до 20 імпульсів водневої плазми. Фазовий склад якісно не змінюється. Показано, що зміни, які відбуваються в покриттях, в основному проявляються як зміни в субструктурі спостережуваних фаз. Структура квазікристалічної ікосаедричної фази з накопиченням імпульсів впливу вдосконалюється, і розмір областей когерентності збільшується. У плівках, що складаються з кристалічних фаз, спостерігається часткове фазове перетворення з перерозподілом компонентів між фазою 2/1 кристала-апроксиманта і фазою α-твердого розчину. Встановлено, що тонкі плівки Ti-Zr-Ni-системи, що містять квазікристалічну ікосаедричну фазу, при радіаційно-термічних навантаженнях у сумі 20 імпульсами менш схильні до утворення тріщин, ніж покриття з кристалічними фазами тієї ж системи.